2016
DOI: 10.1155/2016/5860296
|View full text |Cite
|
Sign up to set email alerts
|

Supercritical Fluid Extract of Spent Coffee Grounds Attenuates Melanogenesis through Downregulation of the PKA, PI3K/Akt, and MAPK Signaling Pathways

Abstract: The mode of action of spent coffee grounds supercritical fluid CO2 extract (SFE) in melanogenesis has never been reported. In the study, the spent coffee grounds were extracted by the supercritical fluid CO2 extraction method; the chemical constituents of the SFE were investigated by gas chromatography-mass spectrometry (GC-MS). The effects of the SFE and its major fatty acid components on melanogenesis were evaluated by mushroom tyrosinase activity assay and determination of intracellular tyrosinase activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…The SCGs showed concerning bioactive components such as insoluble dietary fiber, polysaccharides, lipids, amino acids, proteins, alkaloids, phenolics, minerals, and volatile compounds [6]. The previous investigations have focused on the SCGs' bioactivity and their antioxidant [7], anti-inflammatory [8], dermatological, anti-melanogenesis [9], and metal scavenging properties [10]. The optimum conditions of solid/liquid SCGs-extraction using solvent systems to recover the antioxidant polyphenols were studied [11].…”
Section: Introductionmentioning
confidence: 99%
“…The SCGs showed concerning bioactive components such as insoluble dietary fiber, polysaccharides, lipids, amino acids, proteins, alkaloids, phenolics, minerals, and volatile compounds [6]. The previous investigations have focused on the SCGs' bioactivity and their antioxidant [7], anti-inflammatory [8], dermatological, anti-melanogenesis [9], and metal scavenging properties [10]. The optimum conditions of solid/liquid SCGs-extraction using solvent systems to recover the antioxidant polyphenols were studied [11].…”
Section: Introductionmentioning
confidence: 99%
“…The extractor was loaded in a random way with approximately 12 g of noncompact powdered sample. The extraction parameters of compound were performed by orthogonal array design (OAD) OA 9 (3 4 ) ( Table 1 ) [ 16 ]. In the present work, four factors were studied by a three-level OAD: modifiers, dynamics extraction time, temperature, and pressure.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, the extraction using clean technology is indispensable. In this sense, supercritical fluid extraction is safer for the human being, due to the reduction of the volume of organic solvent and extraction time [16]. Authors have been extracting alkaloids semipurified by supercritical fluid extraction [1719], and we have extracted the pyrrolidine alkaloids with better yield than chloroform [12].…”
Section: Introductionmentioning
confidence: 99%
“…Phosphorylation of the mitogen-activated protein kinase (MAPK) signaling pathways lead to a reduction of melanin synthesis in mouse melanocytes. Several studies suggested that activation/phosphorylation of the extracellular signal-regulated kinase (ERK) and c-Jun N-terminal kinase (JNK) signaling pathways results in the inhibition of melanogenesis ( 10 , 11 ). This effect has been attributed to the phosphorylation of MITF at serine 73, which results in MITF ubiquitination and degradation ( 12 ).…”
Section: Introductionmentioning
confidence: 99%